Ultra-wide tuning single channel filter based on one-dimensional photonic crystal with an air cavity *Project supported by the National Natural Science Foundation of China (Nos. 61575138, 61307069, 51205273), and the Top Young Academic Leaders and the Outstanding Innovative Teams of Higher Learning Institutions of Shanxi. (February 2017) - Zhao, Xiaodan; Yang, Yibiao; Chen, Zhihui; Wang, Yuncai; Fei, Hongming; Deng, Xiao
Abstract: By inserting an air cavity into a one-dimensional photonic crystal of LiF/GaSb, a tunable filter covering the whole visible range is proposed. Following consideration of the dispersion of the materials, through modulating the thickness of the air cavity, we demonstrate that a single resonant peak can shift from 416.1 to 667.3 nm in the band gap at normal incidence by means of the transfer matrix method. The research also shows that the transmittance of the channel can be maximized when the number of periodic LiF/GaSb layers on one side of the air defect layer is equal to that of the other side. When adding a period to both sides respectively, the full width at half maximum of the defect mode is reduced by one order of magnitude. This structure will provide a promising approach to fabricate practical tunable filters in the visible region with ultra-wide tuning range.